(untitled) (International Journal of Studies in Nursing, 2026)
Objective: The purpose of the current study was to determine college students’ stress coping behaviors and perception of stress-effects holistically (emotionally, mentally, and physically). Participants: The current study was conducted using a convenience sample of 120 students in a Midwestern Christian college with a student population of about 2000. Participants were mostly from the education, nursing, and ministry departments. Method: A quantitative, cross-sectional, with a descriptive survey design was most suitable for this study. Results: Students deal with stressors in positive and negative ways. Positive ways included exercise, depending more on faith, and telling themselves that everything will be “Okay.” Negative ways included eating more, sleeping less, increased use of the Internet and more procrastination. Conclusions: College students are aware of constructive ways to cope with stress; however, these techniques are rarely used.